Improve students creative ability in discrete mathematics course with approach open ended assisted visual basic application for excel - M Bernard; T Rosyana; M Afrilianto (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Students are the future generation to develop the technology. Keep in mind, that technology and information is always something to do with mathematics. Difficulties faced today about mathematics is the problem of proof, and it takes the students are led to creative ideas tailored to the definitions and theorems that have been proved. But for the student takes an overview of definitions through mathematical algorithms can be realized and understood by students. One of the subjects relating to proofs is discrete mathematics. The aim here students can understand the integer, number operations, the mathematical logic which is not memorizing but understanding math concepts meaningful based on the development of the student creative process. So that their findings can be a rewarding experience and may be able to develop more extensive utilization of evidence, therefore, researchers Open-Ended approach. To help overview of definitions is needed as delivery tools more effective mathematics which props. Props are used should be Appropriate to the use and purpose of learning, the role of ICTs is needed to convey the image that is associated with VBA for Excel mathematics is an application, the usefulness of affecting data processing.